THU0199 Successful outcomes of pregnancy in patients with ANCA vasculitis. (23rd January 2014) - Croft, A.; Smith, S.W.; Carr, S.; Youssouf, S.; Salama, A.; Pusey, C.; Harper, L.; Morgan, M.
Abstract : Background: There is a paucity of data on the outcome of pregnancy in patients with primary systemic vasculitis. The limited evidence available suggests frequent complications such as first-trimester miscarriages, pre-term births, premature rupture of membranes and relapse of disease resulting in fetal and maternal death. Many of these studies are old and based on isolated case reports. Objectives: To describe the outcome of pregnancies in patients with anti-neutrophil cytoplasmic antibody (ANCA) associated small vessel vasculitis: Granulomatosis with Polyangiitis (GPA) and Microscopic Polyangitis (MPA). Methods: Retrospective case analysis of all women who became pregnant following a diagnosis of ANCA associated vasculitis or whose disease developed de novo during pregnancy in the cohort of patients treated in 3 UK centres. Results: Nine pregnancies were observed in 8 patients following a diagnosis of vasculitis. All patients identified had a diagnosis of ANCA associated vasculitis according to EMEA criteria (7 diagnosed with GPA and one with MPA). All patients were in clinical remission for at least 12 months with low or undetectable serum ANCA titres at the time of conception and had no other risk factors for antenatal complications including proteinuria and hypertension. Five patients received cyclophosphamide induction therapy prior to pregnancy with a cumulative dose between 3-10g. Methotrexate was discontinued in all patients with a planned pregnancy. One patient had a first trimester miscarriage following an unplanned pregnancy whilst taking methotrexate. Seven patients were switched to azathioprine prior to pregnancy in combination with prednisolone. One patient experienced a second trimester disease relapse which was treated successfully with immunoglobulin G and plasmapheresis and progressed with an otherwise uncomplicated pregnancy. Nine live births were observed with all infants born at full term by normal vaginal delivery with the exception of one patient with a twin pregnancy and one patient with a breech presentation who underwent an elective caesarean sections. There were no obstetric or neonatal complications and no disease relapse reported in the post-partum period. Conclusions: Planned pregnancy in ANCA associated vasculitis is safe with a low incidence of fetal and maternal complications. Patients should be in remission at the time of conception and on appropriate immunosuppressant therapy. Disease relapse can be treated successfully without causing fetal complications. Disclosure of Interest: None Declared